The Influence of Islamic Social Reporting and Financial Distress on Tax Avoidance with Profitability as a Mediating Variable: Study on Islamic Commercial Banks - Fatmasari, Ines Muharromah; Dewi, Fajar Gustiawaty; Asmaranti, Yuztitya (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study analyzes the influence of Islamic Social Reporting (ISR) and Financial Distress on Tax Avoidance, with Profitability as a mediating variable, focusing on Islamic Commercial Banks in Indonesia. This quantitative research utilizes secondary data from annual financial reports of banks registered with the Financial Services Authority (OJK) from 2021 to 2023. The sample was selected using purposive sampling, yielding 33 observational data points from 11 Islamic Commercial Banks that met the criteria. Data analysis was performed using descriptive statistics, multiple linear regression, classical assumption tests, hypothesis testing, and the Sobel test with SPSS version 25. The results indicate that ISR has a positive and significant effect on Tax Avoidance, and Financial Distress also positively and significantly impacts Tax Avoidance. ISR is found to have a strong positive effect on Profitability, while Financial Distress negatively affects Profitability. Profitability itself demonstrates a positive effect on Tax Avoidance. Furthermore, Profitability mediates the relationship between ISR and Tax Avoidance, and also significantly mediates the relationship between Financial Distress and Tax Avoidance. These findings suggest that both transparency in socio-religious reporting and the financial condition of companies influence tax avoidance strategies, with profitability playing a crucial role in explaining this behavior.